Investigating the Truths: Inquiries, Conspiracies and Implied Performances in the Public Record - Graham White (Law Text Culture, 2010)
The focus in courtrooms or tribunal chambers on live witness evidence-giving is examined in literature dealing with the residue of legal encounters as a space of potential instability for the process of establishing narrative authority (Auslander 1999; Lynch and Bogen 1996; TDR 2008). These accounts focus on the self-conscious ‘play’ of witness performance — self-presentation, demeanour and verbal and physical fluency as the site of a particular, intractable form of challenge to attempts to construct a definitive legal record. In this essay I will examine some instances in which historically prominent legal proceedings have proved fertile ground for challenges to official narratives through the tendentious reconstruction of such witness performance as implied by the written record. This kind of reconstruction is a common feature of a body of conspiracy theories which read ‘against the grain’ of official narratives.